Living in difficult places: social connections, networks, everyday life & the (re)production of violence - Fontana, SG (2020)
This thesis analyses social dynamics in Masisi, a rural area of eastern Congo, and considers how the relationships on which people rely contribute to the (re)production of violence. The province of North Kivu is often called the epicentre of war; if this is the case, Masisi is its flashpoint. As in many areas of the world where endemic poverty and poor governance are compounded by environmental factors and insecurity, Masisi has endured decades of recurrent political violence. Indeed, in 2007 a controversial report estimated that in the decade between 1998-2008 5.7 million Congolese died of conflict-related causes (Coghlan et al., 2007). A decade later, despite peace accords and the presence of one of the United Nation’s longest and largest peacekeeping mission, violence in eastern Congo continues. /p>